Orange is the new black. Season three [videorecording (DVD)] - Schilling, Taylor, 1984-; Harney, Michael J.; Mulgrew, Kate, 1955- (Lionsgate, 2016)
A new regime has arrived at Litchfield and with it comes new business interests, spiritual movements, and parental problems that turn life behind bars upside down and ignite power struggles among Litchfield's residents and guards.